Prognosis of Gastric Cancer Patients with Node-Negative Metastasis following Curative Resection: Outcomes of the Survival and Recurrence - Jingyu Deng; Han Liang; Dan Sun; Rupeng Zhang; Hongjie Zhan; Xiaona Wang (Canadian Journal of Gastroenterology)
BACKGROUND: The purpose of the present study was to provide valuable prognostic information on lymph node-negative gastric cancer patients following curative resection.